PURWARUPA ALAT PENGHITUNG KERTAS DAN HARGA JASA PEMAKAIAN MESIN FOTOKOPI BERBASIS MIKROKONTROLER AT89S51 - Mulyadi, Mulyadi; Sutikno, Tole; Iswanjono, Iswanjono (Transmisi, 2009)
This paper describe the single chip mode prototype of automatic paper and price counting tool in old type photocopying machine based on AT89S51 microcontroller. The experiment showed the prototype had been design could count how many paper out from photocopying machine and then calculate its price. The number of the paper and calculation result in rupiahs was displayed at LCD screen. This prototype have the ability to count one paper per second and 100% price calculation accuracy.Keywords: microcontroller, AT89S51, paper counting tool, photocopying machinePermalink: http://ejournal.undip.ac.id/index.php/transmisi/article/view/2762